REAKSI PASAR ATAS PENGUMUMAN CORPORATE GOVERNANCE PERCEPTION INDEX PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dyan Kunthi Nalitami (STIE Perbanas Surabaya, 2012)
Objective of this research is empirically examine about the market reaction of Corporate Governance Perception Index announcement which is reflecting from abnormal return and trading volume activity between companies that has rating of Corporate Governance. Perception Index (CGPI) by very trusted companies, trusted companies and trusted enough companies. The sample of this research is 16 very trusted componies, 40 trusted companies and 13 trusted enough companies during the period of 2006-2010 which were drawn using the purposive sampling method. ANOVA is used to test the hypothesis that there are differences between abnormal return and trading volume activity in those three categories of CGPI rating. Closing price and trading volume activity for 7 days at investigating period is used to measure the market reaction in Indonesia Stock Exchange. The result of this research shows that there is no difference between abnormal return, but there is difference on trading volume activity for very trusted companies, trusted companies, and trusted enough companies. It means that information about CGPI announcement isn't good newt for intestor and has no informatbn for investor investment decision making.